Operational Trans-resistance Amplifier based Inductor Simulation - Prasad Tripathy, Hara; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
The present paper relates to “Simulation of an inductor based on Operational Transresistance Amplifiers”. This implantation can be used in place of an actual inductor. In this values of passive elements like resistors and capacitors are varied to vary the values of inductor correspondingly.Virtual grounding is used for passive components. Later in the paper simulated inductor application is deliberated for showing chemistry with extra complicated circuits. Different simulation results are obtained by the experimentation.